Anxiety level and compliance with health protocols during the covid-19 pandemic in Madura Indonesia - Muhammad Rosyidul Ibad; Arfianto, Muhammad Ari; Triandini , Aprillia (Jurnal Keperawatan, 2023)
Introduction: The COVID-19 pandemic has caused changes in various aspects of life, one of which is the culture of implementing health protocols to prevent transmission. The level of anxiety about illness is considered to have a role in adherence to health protocols. There are not many studies that explain the relationship between anxiety levels and adherence to health protocols. Objectives: This study aims to determine the relationship between anxiety levels and adherence to health protocols in the Madura Indonesian. Methods: This study used a cross-sectional design. The number of samples is 400 people of Madura Regency, the samples were selected using purposive sampling technique. The inclusion criteria were at least 17 years old and able to read and write. The research instrument used the Zung Self Rating Anxiety Scale and Adherence to COVID-19 Prevention Measures questionnaires. Results: The level of anxiety was dominated by mild anxiety (49.3%), while adherence to health protocols was dominated by low compliance (44.8%). The results of the Spearman rho test showed that there was a relationship between the level of anxiety and adherence to health protocols with a value of p = 0.000. Conclusions: This study shows that there is a significant relationship between anxiety levels and adherence to health protocols.